2019
DOI: 10.1002/jor.24442
|View full text |Cite
|
Sign up to set email alerts
|

Bone Stress Injuries Are Associated With Differences in Bone Microarchitecture in Male Professional Soldiers

Abstract: Bone stress injuries are commonly due to repetitive loading, as often described in competitive athletes or military recruits. The underlying pathophysiology of bone stress injuries is multifactorial. The present cross-sectional study investigated (i) cortical and trabecular bone microstructure as well as volumetric bone mineral density in subjects with bone stress injuries at the tibial diaphysis, measured at the distal tibia and the distal radius by means of high-resolution peripheral quantitative computed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
(71 reference statements)
0
12
0
Order By: Relevance
“… 46 Our results are only partly in line with previous observations in male soldiers with BSI (n = 26) who had reduced cortical vBMD and trabecular thickness but not cortical thickness. 35 Together, these results suggest that impaired bone microarchitecture may be a relevant risk factor for BSI, but the results regarding the affected bone compartment or specific parameters are inconsistent. Our data suggest alterations occured in the cortical compartment, which became evident by comparison with a control group and adaptation of the parameters to age-, sex-, and device-specific reference data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 46 Our results are only partly in line with previous observations in male soldiers with BSI (n = 26) who had reduced cortical vBMD and trabecular thickness but not cortical thickness. 35 Together, these results suggest that impaired bone microarchitecture may be a relevant risk factor for BSI, but the results regarding the affected bone compartment or specific parameters are inconsistent. Our data suggest alterations occured in the cortical compartment, which became evident by comparison with a control group and adaptation of the parameters to age-, sex-, and device-specific reference data.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have elaborated on the osseous microstructural alterations in athletes with BSI, 1 , 33 , 35 , 36 , 46 albeit no study comprising biochemical, DXA, and HR-pQCT data in a comparable cohort size has been reported thus far. In our study cohort, cortical thickness and area at the distal radius and tibia as well as trabecular bone volume fraction at the distal radius were reduced compared with those in controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is often estimated based on measures of bone mineral density (BMD) and content (BMC; eg, areal or volumetric density) and bone morphology and geometric properties (eg, cortical diameter or bone area). 5,6 Using both DXA and pQCT, Beck et al 5 found that recruits who presented with fractures had poorer physical fitness and body composition, smaller midthigh muscle cross-sectional area (mCSA), and less estimated thigh and tibial bone strength than uninjured recruits. Among college-aged adults at the US Naval Academy, Armstrong et al 4 reported that low total body areal BMD (aBMD) was inversely correlated with fracture risk during 8 weeks of training.…”
mentioning
confidence: 99%
“…Authors of most studies in young-adult military cohorts have assessed differences between those who had already sustained a fracture and those who had not; less research has been conducted on predictors of estimated tibial bone strength using a prospective design. 6 Although DXA and pQCT provide valuable information regarding estimated bone strength, these imaging techniques cannot assess bone cell responses and are not commonly used for military health assessments, thereby reducing their utility.…”
mentioning
confidence: 99%